FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Rochman Arif (STIE Mahardhika, 2020)
The purpose of this research is to test and analyze the influence of human resource variables, supporting devices, leadership styles, organizational commitments and information technology to implement SAP-based accruals in the government of Lamongan Regency. This research was conducted in Lamongan Regency sample in this study as much as 97 respondents consisting of 36 SKPD in Lamongan Regency. Data analysis tools in this study use multiple linear regression analyses , use SPSS App version 20 help. The results of this study showed that the variables of human resources, supporting devices, leadership styles, organizational commitments and information technology to influence the implementation of SAP-based accruals in the government environment of Lamongan Regency. Simultaneously human resources, supporting devices, leadership styles, organizational commitments and information technology in the implementation of the positive effect of SAP based on accruals in the government environment of Lamongan Regency.